2015
DOI: 10.1096/fasebj.29.1_supplement.947.26
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of all Caldesmon Splice Variants in Mice Results in Abdominal Wall Closure Defects

Abstract: Ample evidence obtained in vitro indicates that the thin filament linked protein, caldesmon (CaD) is involved in regulation of smooth muscle contraction. Homozygous h‐CaD deficient mice were reported to be viable and exhibit a but small slowing of relaxation (Guo et al., 2013). However, the results are confounded by upregulation of non‐muscle l‐CaD in smooth muscle. Thus, the in vivo function of CaD is still not clear. Here we report that deletion of all splice variants of Cald1 results in perinatal lethality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Some homozygous Cald1-mutant mice develop spontaneous hernias and die within 5-7 h after birth [15]. The Cald1 knockout fetuses have the persistence of the physiological umbilical hernia whereby the size of the abdominal wall defect is variable [16]. Here we found that risk alleles of 5 GWAS-significant SNPs are associated with decreased expression of CALD1 (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Some homozygous Cald1-mutant mice develop spontaneous hernias and die within 5-7 h after birth [15]. The Cald1 knockout fetuses have the persistence of the physiological umbilical hernia whereby the size of the abdominal wall defect is variable [16]. Here we found that risk alleles of 5 GWAS-significant SNPs are associated with decreased expression of CALD1 (Fig.…”
Section: Discussionsupporting
confidence: 49%